SEBUAH PENCARIAN, MAHASISWA AKUNTANSI YANG AKUNTANSI - Kusumaningtyas, Dian; Puspita, Erna (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
The purpose of this study was to find out how students' perceptions and understanding of accounting. And whether the aspirations of these students are in accordance with their lecture education. This research is a qualitative study in which data collection uses interview techniques. The informants interviewed i were fifth semester students (V) in Accounting Study Program at the University of Nusantara PGRI Kediri. The data analysis technique uses transcendental phenomenology analysis techniques, the translation of which is Noema, Epoche (Bracketing), Noesis, Intentional Analysis and Eidetic Reduction. The results of the study concluded that the informants chose the accounting department because they assumed that the promised employment opportunities were wide. Some informants felt that studying at an accounting study program was difficult because many counts and courses were sometimes difficult to understand. However, the informant also assumed that with accounting courses there was a lot of information about how the financial statements should be presented and how to assess the fairness of financial statements. Besides that what makes them interested is the development of accounting science that is always up to date. Some background informants chose the career they aspired to start from wanting to reduce the occurrence of corruption to be tempted by a large salary. Career planning is needed to determine the direction in accordance with the goals, the lack of understanding of accounting also influences the career aspired by the informant.